O023 Feasibility study to determine the time taken for NAATs tests to become negative following treatment for Chlamydia trachomatis and Neisseria gonorrhoeae in men and women. (30th June 2016) - Sultan, Binta; Oakland, Clare; Brima, Nataliya; Patel, Hemanti; Copas, Andrew; Benn, Paul; Ison, Cathy; Schembri, Gabriel
Abstract : Background/introduction: Few data are available to guide the best time to perform a test of cure using nucleic acid amplification tests (NAATs) following treatment for chlamydia (CT) and gonorrhoea (NG). Aim(s)/objectives: The association between the type of infection, organism load, site of infection and treatment were compared to the time for the NAAT to become negative after treatment. Methods: Individuals who had a positive NAAT test for CT and/or NG were eligible. Self-taken specimens from the site of infection were collected at 8 time points.The time to first negative test following treatment was examined using survival analysis techniques. Results: 102 men (87 MSM) and 52 women were recruited to the study (84 NG, 71 CT infections). 28 participants with NG and 16 with CT were lost to follow up. On day 0, 20 participants diagnosed with NG and 8 diagnosed with CT had negative tests. Median time to negativity for NG infection was 2 days (IQR 1–5) and for CT infection was 4 days (IQR 2–5). At day 14 after treatment 92% of participants were CT negative, and 84% NG negative.All tests were negative by day 35 for both infections. Discussion/conclusion: This study provides valuable data in determining the time to test of cure for CT and NG infections. Site of infection may have an effect on time to clearance of infection, with pharyngeal NG infections and vaginal CT infections taking longer to clear than other sites.The results of this study will help guide clinicians to the timing for test of cure.